Interleukin-1 Receptor Modulation Using β-Substituted α-Amino-γ-Lactam Peptides From Solid-Phase Synthesis and Diversification - Geranurimi, Azade; Cheng, Colin W. H.; Quiniou, Christiane; Côté, France; Hou, Xin; Lahaie, Isabelle; Boudreault, Amarilys; Chemtob, Sylvain; Lubell, William D. (Frontiers in Chemistry, 2020)
As a key cytokine mediator of inflammation, interleukin-1beta (IL-1beta) binds to the IL-1 receptor (IL-1R) and activates various downstream signaling mediators, including NF-kapaB, which is required for immune vigilance and cellular protection. Towards the development of IL-1-targeting therapeutics which exhibit functional selectivity, the all-D-amino acid peptide 1 (101.10, H-D-Arg-D-Tyr-D-Thr-D-Val-D-Glu-D-Leu-D-Ala-NH2) was conceived as an allosteric IL-1R modulator that conserves NF-kapaB signaling while inhibiting other IL-1-activated pathways. Employing β-hydroxy-α-amino-γ-lactam (Hgl) stereoisomers to study the conformation about the Thr3 residue in 1, [(3R,4S)-Hgl3]-1 (2b), among all possible diastereomers was found to exhibit identical in vitro and in vivo activity as the parent peptide and superior activity to the α-amino-γ-lactam (Agl) counterpart. Noting the relevance of the β-hydroxyl substituent and configuration for the activity of (3R,4S)-2b, fifteen different β-substituted-Agl3 analogs of 1 (e.g., 2c-q) have now been synthesized by a combination of solution- and solid-phase methods employing N-Fmoc-β-substituted-Agl3-Val-OH dipeptide building blocks. Introduction of a β-azido-Agl3 residue into the resin bound peptide and subsequent reduction and CuAAC chemistry gave access to a series of amine and triazole derivatives (e.g., 2h-q). β-Substituted-[Agl3]-1 analogs 2c-q exhibited generally similar circular dichroism (CD) spectra as that of Hgl analog 2b in water, presenting curve shapes indicative of β-turn structures. The relevance of the β-substituent was indicated in rodent models of preterm labor and retinopathy of prematurity (ROP), in which certain analogs inhibited preterm birth and vaso-obliteration, respectively, with activity similar to 1 and 2b. The β-substituted-[Agl3]-1 analogs exhibited functional selectivity on IL-1-induced signaling pathways. The described solid-phase method has provided discerning probes for exploring peptide structure-activity relationships and valuable leads for developing prototypes to treat inflammatory events leading to prematurity and retinopathy of prematurity, which are leading causes of infant morbidity and blindness, respectively.